The Education Existence During Sinabung Eruption Emergency Period - Dahliana, Ermita; Sinaga, Marlon (Sumatra Journal of Disaster, Geography and Geography Education, 2018)
This study aims to collect, process, analyze and describe the profile of education in emergency relief Sinabung Volcano eruption. This study is a descriptive study using qualitative data. Data were collected by using interview techniques, observation and documentation. This research perform about profile about education at SMA Negeri 1 Simpang Empat. Results illustrate that the profile of education in emergency relief in terms of the learning process should not be running optimally sebagaiman, educational facilities were damaged so it can not be used anymore, formal and informal education should be evacuated to a safer place.